Forord - Thodberg, Christian (Grundtvig-Studier, 1977)
For the Sake of Continuity Words and Motifs in Grundtvig’s Hymns and Sermons - Introduction by Christian Thodberg The majority of the papers in this book have been written between 1975 and 1977 as special studies at the Institute of Practical Theology in connection with a course on Grundtvig’s hymns and sermons. The starting-point was Christian Thodberg’s previous studies on the fixed correlation between word and motif in Grundtvig - patterns which appear with such deliberateness and regularity that numerous words and concepts in Grundtvig are coloured by way of result and acquire a particular meaning purely from their context. This is apparent in the role that a major structure such as the baptism ritual plays. But it is equally true of the smaller structures, for example the regular linking of individual words to such words as hearty hope, peace, mouth, ear, etc. As a ‘catalogue’ for our first term’s work we used the hymn Lyksaligt det folk, der har øre for klang (.Blessed is the people with an ear for sound). We chose the hymns as our first area of research because they contain the most explicit form of words and concepts for the purpose. But the fixed connection between sermon and hymn in Grundtvig led of its own accord to an inclusion of the sermons - both those published and in particular those unpublished. It is in the sermons that Grundtvig stubbornly and diligently formulated his concepts, and it is in this connection that the hymns are time and again the crowning glory. By concentrating on central words that appear with definite regularity we have aimed at reaching a clearer definition of a particular word or concept in Grundtvig s context and on Grundtvigs premises. It has been interesting to observe that particular wordpatterns are only built up gradually, thus opening up the possibility of pointing out lines of development hitherto overlooked.